Improving accuracy of asphalt content determination by ignition test. (24th November 2017) - Rodezno, Carolina; Brown, Ray
Abstract : Accurate determination of asphalt content and aggregate gradation is critical for controlling quality of asphalt mixtures during construction. Most state specifications require quantitative evaluation of the asphalt content of mixes as a criterion for acceptance. The ignition oven test procedure specified in AASHTO T 308 (Standard method of test for determining the asphalt binder content of Hot Mix Asphalt [HMA] by the ignition method) is required or allowed by most state DOTs for determining the asphalt content and aggregate gradation of asphalt mixtures. The ignition oven test specified in AASHTO T 308 procedure requires the determination of asphalt content correction factors for each asphalt mix and for each ignition oven used. However, in some instances when numerous asphalt mix designs and several ignition ovens are available, correction factors (CFs) are shared between ignition units, even when that practice is not allowed by the standard. There is a need to identify the consequences of sharing correction factors between units/mixes and also to identify testing parameters that affect the measured CFs. By identifying possible causes of variation, the test procedure could be adjusted to make the CFs more consistent between ignition ovens. Also, it should be possible to reduce the amount of difference in CFs between all types of equipment. A study was conducted to assess the variability of ignition oven CFs for different ignition oven unit brands and mixes to better understand the implications of sharing CFs. Twenty-three laboratories used various brands of ovens to test four mixes containing aggregates with varying CFs. The results indicated that CFs were significantly different for the different mixes even when the same unit brand was used. The within-lab and between-lab precision developed in this study suggests that different precision statements are necessary for aggregates with high breakdown potential and that the current precision included in AASHTO T 308 was likely developed for low weight loss aggregate making it unacceptable to use for aggregates with higher CFs. It was also found that the addition of lime caused no significant difference in the measured asphalt content when the CF was correctly measured. However, it was cautioned that a change in amount of lime during mixture production would affect the measured asphalt content. In addition, ways to minimise variability in asphalt CF were evaluated. It was determined that ignition tests conducted at lower temperature (427°C) proved to be effective in reducing the variability in measured asphalt content since the lower temperature reduced the asphalt correction factors for asphalt mixes.